INCLUSIVE EDUCATION AS A FORM OF HUMANIZED EDUCATION - Matupayeva Sh. Z. (Web of Journals Publishing, 2024)
Pedagogical problems between parents, students and personnel regarding the introduction of inclusive education are discussed in the article.
Keywords: yоrdаmgа muhtоj о‘quvсhi, korreksion sinf, insonparvarlik, oila, inklyuziv ta’lim.